Penerapan Metode Rapid Application Development untuk Perancangan Sistem Informasi Penagihan Piutang Premi Asuransi - Badrul, Mohammad; Dewi, NurHikmah Sari (STIKOM Tunas Bangsa Pematangsiantar, 2020)
One of the business actors, in this case, is that the company is required to consider reducing the risks faced. One of them is PT. Indopratama Jaya Mandiri is a company engaged in consulting and insurance claims. In the billing process, it is no longer possible to use the help of the Ms. application. Excel for the data, as well as customer billing that is paid more than once, either to direct insurance or to the company. The information generated requires a long time. This can have an impact especially on the billing department, which can result in a waste of time and costs and other errors due to the payment process that uses two vendors. Method of Rapid Application Development (RAD) The author chose because this method has the advantage of being able to obtain the right system because the system is divided into several versions and the most important functions to be tested. The results obtained are information systems that can overcome problems that have been faced by companies related to insurance billing to customers.